A step-by-step introduction to statistics for business - Landers, Richard N. (Los Angeles ; London Sage, 2019)
"This book will help to equip business students with the knowledge and skills required to succeed in their studies and confidently use statistics in the workplace."--Publisher's description.
Prologue: review of essential mathematics -- Part 1: Descriptive statistics. The language of statistics -- Working with numbers and data display -- Central tendency and variability -- Probability distributions -- Sampling distributions -- Part 2: Inferential statistics. Estimation and confidence intervals -- Hypothesis testing -- z-Tests and one-sample t-tests -- Paired- and independent-samples t-tests -- Analysis of variance (ANOVA) -- Chi-squared tests of fit -- Correlation and regression -- Part 3: Wrap-up. Matching statistical tests to business problems.
First published 2013.
Includes index.
Keywords: Commercial statistics